Photoelectron spectroscopy of low valent organophosphorus compounds, P–CH3, H–PCH2 and PCH2. Issue 18 (25th April 2022) - Mukhopadhyay, Deb Pratim; Gerlach, Marius; Hartweg, Sebastian; Fischer, Ingo; Loison, Jean-Christophe
Abstract : We report the mass-selected slow photoelectron spectra of three reactive organophosphorus species, PCH2, and the two isomers, methylenephosphine or phosphaethylene, HPCH2 and methylphosphinidine, P–CH3 . Abstract : We report the mass-selected slow photoelectron spectra of three reactive organophosphorus species, PCH2, and the two isomers, methylenephosphine or phosphaethylene, HPCH2 and methylphosphinidine, P–CH3 . All spectra were recorded by double imaging photoelectron–photoion coincidence spectroscopy (i 2 PEPICO) using synchrotron radiation and all species were generated in a flow reactor by the reaction of trimethyl phosphine with fluorine atoms. Adiabatic ionisation energies of 8.80 ± 0.02 eV (PCH2 ), 10.07 ± 0.03 eV (H–PCH2 ) and 8.91 ± 0.04 eV (P–CH3 ) were determined and the vibronic structure was simulated by calculating Franck–Condon factors from optimised structures based on quantum chemical methods. Observation of biradicalic P–CH3 isomer with its triplet ground state is surprising because it is less stable than H–PCH2 .